Local Community Economic Independence in The Ex-Prostitution Area: The Effect of Dolly Closure - Rahma, Rezka Arina; Rasyad, Ach.; Zulkarnain, Zulkarnain; Sumintono, Bambang (Universitas Negeri Semarang, 2022)
This paper seeks to explore the economic independence of local community affected by the closure of Dolly prostitution Surabaya. This paper employed qualitative design with case study approach. It took ten people who own and manage Small and Medium Enterprises as the research subject purposively. They were involved since they are the local community around Dolly and affected by the closure of the prostitution. This research was conducted between June and July 2019. The data were obtained through observation, in-depth interview, and documentation. The data were analyzed by employing Miles and Huberman model consisting of three steps: data condensation, data presentation, and drawing conclusion or verification. The results of the research confirm that most of the local community around Dolly which were affected by the closure of the prostitution indicate an economic independence seen from: (1) the initiative of the local community in developing their business, (2) the satisfaction of the local community from the business they manage after the prostitution closure, (3) the willingness and intention to develop the business, and (4) the beliefs of the local community in developing the business even without the support from the local government. However, this study also confirms that the problem-solving of the local community remains insufficient. Most of them still rely on the government, particularly for the issues of marketing and business place. Thus, as much as 20% of the informants were afraid of the changing of city mayor would impact their business.